A novel artificial tissue simulator for endoscopic submucosal resection training – a pilot study. Issue 1 (December 2016) - Chen, Ming-Jen; Wang, Horng-Yuan; Chang, Chen-Wang; Lin, Ching-Chung; Chen, Chih-Jen; Chu, Cheng-Hsin; Wang, Tsang-En; Shih, Shou-Chuan
Abstract Background We developed a novel artificial simulator for endoscopic submucosal dissection (ESD) as a bridge between instructional videos and animal tissue training and aimed to evaluate the feasibility of using an artificial tissue model in ESD training. Methods Eight gastroenterology fellows from one medical center were enrolled in this ESD training program. Before and after the simulator training, attendees indicated on a 5-point scale the degree of difficulty in performing the following procedures: lesion marking, mucosal pre-cutting, circumferential incision, submucosal dissection, and hemostasis. After the simulator training, the participants completed a questionnaire regarding their opinions on the degree of realism and the feasibility of using this model for training. Results After watching an instructional video, attendees felt that the most difficult techniques were submucosal dissection and hemostasis. After using the artificial tissue simulator model, the attendees felt more confident in performing performing lesion marking (p  = 0.026) and submucosal dissection (p  = 0.037). However, they still felt that hemostasis was the most difficult techniques to master. Overall, the attendees thought the simulator was realistic in simulated lesion marking and its use was feasible for simulated lesion marking and submucosal dissection. Conclusion Our pilot study shows the feasibility of using a novel artificial tissue in performing ESD and we believe that the artificial tissue simulator acts well as a bridge between instructional videos and animal model training. The model is reusable and inexpensive, and could disseminate the techniques of the ESD more easily and quickly.